Quantum dot lasers - Patel, R (2017)
Here we present direct investigation of the lasing behaviour by performing gain spectroscopy of solution-based CQDs enabled via in-situ tuning of the feedback wavelength of an open-access hemispherical microcavity. The investigation is performed on two different types of CQDs, namely spherical CdSe/CdS core-shell CQDs and nanopletelets (NPs). The lasing threshold and the differential gain/slope efficiency of the fundamental cavity mode are measured as a function of their spectral position over a spectral range of ∼ 32 nm and of ∼ 42 nm for the spherical CQDs and NPs, respectively. The results of the gain spectroscopy are described using theoretical models, providing insights into the mechanism governing the observed lasing behaviour. Furthermore, the open-access cavity architecture provides a very convenient way of producing in-situ tunable lasing, and single-mode lasing of the fundamental cavity mode over a spectral range of ∼ 25 nm and ∼ 37 nm is demonstrated using spherical CQDs and NPs, respectively. In addition, the stability of laser emission is investigated, with the lasing intensity of the fundamental cavity mode remaining constant over a time period of almost 6 mins. It is hoped that the results will provide a detailed understanding of the lasing behaviour of CQDs. This information can be fed back into the design of CQDs in which the lasing threshold can be reduced to the point where useful devices can be constructed, and in the design of resonant optical feedback structures for which the appropriate wavelength must be carefully selected.